Kin Altruism, Psychological Contract and Commitment in Immigrant Businesses: Some Theoretical Propositions - Yang, Chulguen Charlie (QRBD, 2014)
Keywords: dept.mgt; peer-reviewed

Gossip in organizations: from an evolutionary psychological perspective - Yang, Chulguen; Minjock, Robert; Voss, Bernard Edward; Colarelli, Stephen M (Academy of Management Proceedings, 2014)
Gossip is often portrayed as a trivial and even destructive behavior at work. This paper integrates previous studies on gossip using a multilevel evolutionary framework and proposes a few empirical propositions to develop a more balanced view on gossip as a medium of informal communication in organizations.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/079-776-281-946-710
Keywords: Evolutionary framework; Informal communication; dept.mgt